A Taxonomy and performance comparison of Cryptography Techniques - Dr. Shivani Joshi, Mohit Tiwari , Dr. Avinash Dwivedi (International Journal of Advanced Science and Technology, 2020)
In the world of digital era, networking and wireless network plays an important role. The security of data is very important send by different means from sender to receiver over transmission media. Though the data is send over seven or five layer protection method by using TCP handshaking protocol. Still network security is for , confidentiality of data and integrity to protect against unauthorized access and use, we use information hiding. This information hiding can be done through Steganography or encryption method called as Cryptography. In this paper we have used the steganography and cryptography techniques to provide security to the wireless network. There are various cryptography techniques like symmetric and asymmetric.